Forest-tree genetics research: Quercus L. - Irgens-Moller, H (Economic Botany, 1955)
Oaks are the sources, not only of the most valuable timber among broad-leaved trees of the northern hemisphere, but also of cork, tannin, a dye, and food for man and beast. Their prolonged pre- flowering periods and other factors have discouraged genetic in- vestigation of them, but what little is known in that direction is here summarized.
Keywords: Hybridization; oak products; oak trees (Quercus spp.); propagation